Does the presence of a normal vaginal pH role out the diagnosis of bacterial vaginosis? - Tilli, Miguel; Orsini, Adrián; Alvarez, María Marta; Almuzara, Marisa; Gallardo, Elena; Mormandi, Juan O. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: bacterial vaginosis (BV) is a vaginal infection characterized by alteration of the vaginal environment with diminish in vaginal content of Lactobacillus spp, and an overgrowth of another microorganism ( anaerobics, Gardnerella vaginalis, Mobiluncus spp. y Mycoplasm). This infection can produce gynaecological and obstetrics complication. Presently the diagnosis of BV is based either on Amsel criteria (clinicalmicrobiological) or as well on Nugent Criteria (microbiological). The measure of vaginal pH through pH reactive indicators is a simple tool and very low cost to be applied in the different level of medical attention. Having in account that it is one of the BV criteria, its normality could be useful to role out the presence of this pathology. Objective: to estimate the value of sensibility, specificity, predictive positive value and predictive negative value of vaginal pH for the diagnosis of BV. Method: it was evaluated in a retrospective way through date obtained from clinical records of the patients derived to Gynaecology Infectious Control consultory room with or without symptoms of vaginal infection to microbiologic studies. It was included 633 patients in this study form January 2002 up to June 2004. Microbiological studies: it was perfomed in all cases a vaginal swab for microscopic examination, pH determination and amine test. Gold standard: for the diagnosis of VB (positive case) it was used Amsel criteria (homogenious discharge, vaginal pH >4.5, positive amine test and the presence of clue cells). For the diagnosis of habitual flora (negative case), it was used the conventional microbiological criteria: pH<4.5, negative amine test, presence of gram–positive bacillus with morphology of Lactobacillus spp. PH vaginal test positive: patients whose pH > 4.5, and negative: those patients whose pH <4.5. Statistical analysis: it was calculated the sensibility, specificity, predictive positive value (PPV) and predictive negative value (PNV). Results: it was included for the analysis 633 patients from wich 230 had BV and 403 habitual flora (HF). The vaginal pH was high in 226 cases of BV and only in 4 cases was normal (negative false). Instead in the HF group the pH was normal in 315 patients and high in 88 cases (positive false). The sensibility of vaginal pH was 98.26% and its specificity 78.16 %. The PPV was 71.97%, and PNV: 98.74%. Conclusion: the vaginal pH evaluation a unique tool for the diagnosis of BV has a high sensibility (98.26%). Due to the high negative predictive value (98.74%) allow us to assert that when the test is normal (pH<4.5) we have a low probability that the patient suffer from BV. Its use for the screening in asintomatic patients is highly trusty to role out the presence of this infection.